Recurrent basal cell carcinoma with maxillary bone invasion - Sampurna, Adhimukti T.; Riani, Eva; Kristanti, Inge Ade; Dwina, Yayi; Ohara, Kuniaki (Journal of General - Procedural Dermatology and Venereology Indonesia, 2019)
Background: Basal cell carcinoma (BCC) is a malignant, slow growing, and locally invasive skin tumor. Advanced and neglected BCC may invade adjacent structures. The 5-year recurrence rates of facial BCCs are 4.1% after excision and 2.5% after Mohs Micrographic Surgery (MMS). The number of BCC cases invading the bones of the head and neck region is limited. Case Illustration: A 75-year-old male complained of bleeding and ulcer enlargement on the right cheek expanding to the right nasal ala for 1 month. The patient had a history of an enlarged and painful lenticular nodule with a hyperpigmented spot that appeared 10 years ago on the right cheek and was diagnosed as BCC. The patient was treated with a wide excision having a negative pathological margin 3 years ago. He noticed that the similar lesion reappeared at the same location 2.5 years ago. Post-operative histopathological results showed nodular infiltrative BCC and maxillary bone invasion. Discussion: Based on history taking, physical examination, and diagnostic evaluation, the diagnosis of the patient was recurrent nodular infiltrative BCC. The final histopathology confirmed that tumor cells invaded the maxillary bone. After considering the treatment options, the patient opted to proceed with radiotherapy. Conclusion: Recurrent nodular BCC with invasion to the maxillary bone is a rare and interesting case. Among 140 BCC cases that we treated with MMS in our hospital from June 2014 to September 2019, this case is the first recurrent BCC with maxillary bone invasion.